ELIANA'S ENVIRONMENTAL AWARENESS IN TERE LIYE'S NOVEL SI ANAK PEMBERANI - Kusumastuty, Imelda; Rianugraha, Yose (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2023)
The issue of environment is a universal and global issue nowadays. The efforts to protect environment are not only conducted through activities in real life. At present, there are a lot of encouragements to raise the environmental awareness through literature since the very beginning, especially the ones intended for young readers. While enjoying the story, the readers are expected to gain also some awareness about the importance of protecting the environment. Asian countries are sometimes considered left behind in portraying the present situation of our environment; therefore, the main objective of this research is to show that the issues of environment are also portrayed in Asian novels for young readers. Hereby, this research is aiming at identifying the social awareness of Eliana, the teenage main character in the novel Si Anak Pemberani (The Brave Girl), and her efforts to protect environment in her village. This novel is written by one of Indonesian outstanding writers, Tere Liye. The research is conducted using ecocriticism. The result shows that Eliana does have awareness toward the environment and she does some efforts to protect it.